Plasma-derived extracellular vesicles contain predictive biomarkers and potential therapeutic targets for myocardial ischemic (MI) injury - Cheow, Esther Sok Hwee (2018)
Myocardial infarction (MI) triggers a potent inflammatory response via the release of circulatory mediators, including extracellular vesicles (EVs) by damaged cardiac cells, necessary for myocardial healing. Timely repression of inflammatory response are critical to prevent and minimize cardiac tissue injuries, nonetheless, progression in this aspect remains challenging. The ability of EVs to trigger a functional response upon delivery of carried bioactive cargos, have made them clinically attractive diagnostic biomarkers and vectors for therapeutic interventions. Using label-free quantitative proteomics approach, we compared the protein cargo of plasma EVs between patients with MI and from patients with stable angina (NMI). We report, for the first time, the proteomics profiling on 252 EV proteins that were modulated with >1.2-fold after MI. We identified six up-regulated biomarkers with potential for clinical applications; these reflected post-infarct pathways of complement activation (Complement C1q subcomponent subunit A (C1QA), 3.23-fold change, p = 0.012; Complement C5 (C5), 1.27-fold change, p = 0.087), lipoprotein metabolism (Apoliporotein D (APOD), 1.86-fold change, p = 0.033; Apolipoprotein C-III (APOCC3), 2.63-fold change, p = 0.029) and platelet activation (Platelet glycoprotein Ib alpha chain (GP1BA), 9.18-fold change, p < 0.0001; Platelet basic protein (PPBP), 4.72-fold change, p = 0.027). The data have been deposited to the ProteomeXchange with identifier PXD002950. This novel biomarker panel was validated in 43 patients using antibody-based assays (C1QA (p = 0.005); C5 (p = 0.0047), APOD (p = 0.0267); APOC3 (p = 0.0064); GP1BA (p = 0.0031); PPBP (p = 0.0465)). We further present that EV-derived fibrinogen components were paradoxically down-regulated in MI, suggesting that a compensatory mechanism may suppress post-infarct coagulation pathways, indicating potential for therapeutic targeting of this mechanism in MI. Taken together, these data demonstrated that plasma EVs contain novel diagnostic biomarkers and therapeutic targets that can be further developed for clinical use to benefit patients with coronary artery diseases (CADs).